STUDY ON REGIONAL FLOOD DISCHARGE REDUCTION USING INFILTRATION WELLS (CASE STUDY OF PERUMAHAN TAMAN ALAMANDA INDAH IN MEDAN) - robi arianta sembiring; Dicky A. Sembiring; Ronald L. Siregar (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
Urbanization is one of the factors that cause an increase in the number of residents in urban areas. The increase of population has an impact on increasing settlements which result in changes in land use. One of the residential areas in Medan City is Perumahan Taman Alamanda Indah which is located in Tanjung Selamat, Medan Tuntungan District. Around 60.7% of the area of Perumahan Taman Alamanda Indah is a closed area in the form of houses and roads which causes high surface runoff when heavy rain occurs. The study aims to plan infiltration wells that can function to reduce flood discharge in Perumahan Taman Alamanda Indah area. The planned infiltration well is a communal well that is divided into several zones. It is planned that 50% of the maximum discharge of rain that falls on the roof of the house is absorbed into the infiltration well. From the results of the study, the required number of infiltration wells is 430 units with a diameter of 1 m and a depth of 2 m which is divided into 13 zones. The construction of this infiltration well can reduce the peak discharge in housing by 36.71%.Key words: land use, infiltration wells, flood